Design Of Two-Stage On/Off Cartridge Valves For Mobile Applications. (September 2017) - Zardin, Barbara; Borghi, Massimo; Cillo, Giovanni; Alberto Rinaldini, Carlo; Mattarelli, Enrico
Abstract: Cartridge valves are widely used in mobile applications, where they are screwed in manifolds, to realize opportune circuit layouts. These valves are quite simple in operation but require a sophisticated design in order to meet all the requirements needed in the mobile machines. Typically, the design process is developed realizing a first design concept and some prototypes and experimentally testing them; after this, the designer chases the optimal performances requested to the valve with a trial and error approach on the prototypes, involving high time and cost resources. In this paper an alternative design procedure is proposed, which involves dedicated simulations to analyze the main critical issues regarding the cartridge valve object of the study. Modelling and simulations here have been considered as steps into the design process of a new valve, which satisfies the requirements and well adapt to the necessities to operate at higher flow and pressure levels without compromising its performances. In that way, the number of prototypes, realized to validate the numerical results and verify the design process, has been considerably reduced, together with related time and costs.